2011
DOI: 10.1074/jbc.m110.200113
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Exopolysaccharide from the Biofilm of Thermus aquaticus YT-1 Induces the Immune Response through Toll-like Receptor 2

Abstract: Bacterial polysaccharides are known to induce the immune response in macrophages. Here we isolated a novel extracellular polysaccharide from the biofilm of Thermus aquaticus YT-1 and evaluated its structure and immunomodulatory effects. The size of this polysaccharide, TA-1, was deduced by size-exclusion chromatography as 500 kDa. GC-MS, high performance anionexchange chromatography with pulsed amperometric detection, electrospray ionization-MS/MS, and NMR revealed the novel structure of TA-1. The polysacchari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 46 publications
2
36
0
1
Order By: Relevance
“…Therefore, further analysis will be needed to determine the mechanisms by which GalNAc and GlcNAc are phosphorylated. GalNAc is a constituent of the cell wall, lipopolysaccharides and exopolysaccharides in bacteria (Tallon et al, 2003;Bernatchez et al, 2005;Freymond et al, 2006;Lin et al, 2011), and it connects glycan chains with the protein backbone of mucins in humans (Jensen et al, 2010). Even though GalNAc is an available source of carbon and nitrogen for bacteria, its catabolic pathway has only been characterized in Escherichia coli and Shewanella sp.…”
Section: Et Al 2009mentioning
confidence: 99%
“…Therefore, further analysis will be needed to determine the mechanisms by which GalNAc and GlcNAc are phosphorylated. GalNAc is a constituent of the cell wall, lipopolysaccharides and exopolysaccharides in bacteria (Tallon et al, 2003;Bernatchez et al, 2005;Freymond et al, 2006;Lin et al, 2011), and it connects glycan chains with the protein backbone of mucins in humans (Jensen et al, 2010). Even though GalNAc is an available source of carbon and nitrogen for bacteria, its catabolic pathway has only been characterized in Escherichia coli and Shewanella sp.…”
Section: Et Al 2009mentioning
confidence: 99%
“…However in vitro studies using EPSs derived from other bacteria, even those which are not present in mammalian GITs, may offer insights into the receptors of and signaling pathways modulated by EPSs. For example, Lin et al [55] published an in vitro study using TA-1, an EPS from the Gram-negative, rod-shaped thermophile Thermus aquaticus and showed that incubation of high quantities of TA-1 with murine RAW 264.7 macrophages or peritoneal macrophages resulted in NF- activation and production of pro-inflammatory TNF- and IL-6 [55] . This inflammatory response was dependent on TLR2, suggesting that TA-1, which is comprised of tetrasaccharide-repeating units of galactofuranose, galactopyranose, and Nacetylgalactosamine (1:1:2) acts as a TLR2 ligand [55] , and mediates its response through NF- Although T. aquaticus is not a mammalian commensal, it functions via TLR2, similar to PSA from B. fragilis and EPS from B. subtilis.…”
Section: Molecular Mechanisms Of Protectionmentioning
confidence: 99%
“…One is biofilm formation, which confers protection against environmental stresses such as high temperature and the presence of antibiotics (8). In previous studies, a novel exopolysaccharide, TA-1, was isolated from a T. aquaticus YT-1 biofilm, and both its primary structure and its immunological activity were determined (13). In addition, we showed that the overexpression of uridine diphosphate (UDP)-galactose-4Ј-epimerase (GalE), which catalyzes the reversible interconversion of UDP-galactose and UDP-glucose, in T. thermophilus HB27 increases biofilm production because of the enzyme's involvement in an important step of exopolysaccharide (EPS) 1 biosynthesis (14).…”
mentioning
confidence: 99%